XRF based barium and aluminium calibrated by punctual solution based ICP-OES analysis of IODP Site U1537 - Hallmaier, Moritz; Gutjahr, Marcus; Lippold, Jörg; Hemming, Sidney R; Gerber, Lukas; Weber, Michael E; Eisenhauer, Anton (In: Hallmaier, M et al. (2025): Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982959, 2025)
Bulk element concentrations were measured for a subset of samples on aliquots after digestion on an ICP-OES (Agilent 700 Series) at the Institute of Earth Sciences, Heidelberg University to calibrate XRF data. Biogenic Barium (Babio) was calculated from Ba and Al concentrations following Nürnberg et al. (1997) with a detrital Ba/Al factor of 0.0067.
Keywords: authigenic uranium; Biogenic Barium (xsBa); bottom-water oxygenation; export productivity; opal; Scotia Sea; sediment; Southern Ocean; Th; thorium normalization; Weddell Sea